Mindfulness for adulting. (2nd January 2018) - Bai, Heesoon; Cohen, Avraham; Miyakawa, Muga; Falkenberg, Thomas
ABSTRACT: This paper calls for ethical responsibility to manifest a holistic, embodied, and deeply relational vision of what it means to actualise fuller human flourishing than how we, humanity as a whole, are behaving currently. A thesis is presented that humanity is experiencing an arrest within the trajectory of species' psychological development and that mindfulness cultivation can facilitate transformation. This thesis comes with a proviso that mindfulness needs to be taken up differently from the dominant discourse around it. A case is made that contemporary mindfulness is most often implicitly and explicitly fuelled by conventional "ordinary consciousness" whose primary function is survival supported by the fear-driven fight–flight–freeze neural assemblage. Suggestions are made that mindfulness be understood as a way of accessing non-ordinary consciousness that sees the world relationally in terms of expansive self-other integration. For this, further suggestions are made that mindfulness be placed back into a larger context, for example, practice-based Buddhist philosophy and psychology, that addresses existential suffering and proffers a comprehensive holistic educational programme. Such a programme cultivates human potential and supports relationally generous and generative human flourishing. As a concrete practice proposal for transitioning into a relational paradigm, inner work is proposed and illustrated with examples.